Links between learning goals, learning activities, and learning outcomes in simulation-based clinical skills training: a systematic review of the veterinary literature - Veenema, Neeltje J.; Hierck, Beerend P.; Bok, Harold G. J.; Salvatori, Daniela C. F. (Frontiers in Veterinary Science, 2024)
IntroductionIn veterinary education programs it is important to have a balance between providing students with valuable hands-on experience and ensuring the ethical treatment and welfare of the animals involved. In the last years simulation-based veterinary education played an important role helping with the replacement of experimental animals in education and at the same time creating a safe learning environment offering endless options for training in a safe environment. The aim of this systematic review was to discern which type of learning outcomes are used to evaluate specific learning goals of clinical skills training and to grasp the impact of diverse simulator characteristics on the measured learning outcomes in clinical skills training.MethodsA systematic search from 1977 until November 2023 has been conducted resulting in 103 included papers. The categories, learning goals, learning activities, and learning outcomes in clinical skills training were used for data extraction of all included studies.ResultsThis study investigated the interplay between learning goals, learning activities, and learning outcomes. Competence and knowledge were the most frequently described learning outcomes; static and screen-based simulators are the are most frequently used technologies. Static simulators are primarily used to train procedural steps and screen-based simulators are primarily used to train relevant knowledge and clinical reasoning. Notably, none of the reviewed studies made explicit connections between learning goals, learning activities, and learning outcomes.DiscussionIn simulation-based education it is important to provide a structured, constructively aligned process where students gain relevant and effective experience. The results of this study underscore the importance of aligning the learning process in simulation-based clinical skills training, and that alignment in the learning process is not always evident.